Basic lingvopoetic analysis of works of Iliya Bakhtiya. (Eurasian Journal of Philology Science and Education, 2015)
The article discusses the work of Uighur poet Ilya Bakhtiya, also analyzes poems belong to different themes. The author presents the difference between the types of analysis of literary works such as linguistic, and lingvostilystics, lingvopoetics and illustrates them with examples. Iliya Bakhtiya’s works such as satire, poetry, civil poetry, children's poetry have been carefully researched and have been analyzed. Based on the skills of the poet and rich language, we can call him as a national poet. The author also examines the role of the poet in Uighur literature and does extensive research on the poet's work. The article may be useful resource for young researchers in philology and in particular on the study of literature.
Keywords: Works of Iliya Bakhtiya; lingvopoetics; linguostylistics; poetry; children's poetry.